Workshop Pilah Sampah Sebagai Kampanye Peningkatan Kesadaran Lingkungan Bersama Rapel Solo Raya - Haryono, Novita; Arzil, Andrine Prima Afneta; Suminar Ayu, Aulia; Hastjarjo, Sri; Widyantoro, Widyantoro; Arifin, Hamid; Pawito, Pawito (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
The community has the right to get a clean, beautiful, comfortable and healthy environment; get cleaning services; utilizing and processing waste; actively participate in waste management activities; and obtain information from local governments and/or other parties that are directly related to the sustainability of life related to waste. This right has direct implications for the community's obligations regarding the management of household waste and/or similar household waste by being obliged to reduce and/or handle waste in an environmentally sound manner. Unfortunately, the handling of environmentally sound waste has not gone well due to inadequate facilities, enforcement of regulations, and low awareness of the community itself. PT. Wahana Anugerah Energi has developed a waste collection and transportation system using a smartphone application called Rapel. Rapel campaigns for sustainable waste management in households. Currently, Rapel provides garbage pick-up services, especially for recycled waste. However, the problems faced include: wide community reach but with Human Resources (HR) PT. The Wahana Anugerah Energi (Rapel Surakarta) is limited, facilities and infrastructure for the ongoing development of understanding of waste management for the community are not sufficient, the application of Rapel is not yet known by the people of Surakarta. overcome, the lack of public awareness of Surakarta City regarding waste management, lack of cooperation and coordination with agencies related to waste problems so that Rapel technology has not received public knowledge, Surakarta people do not know about data integration related to environmental information. From this problem, we design a social marketing communication program so that Rapel Indonesia's goal of encouraging people to sort household waste can be achieved. To achieve this, we design a waste sorting workshop by presenting credible sources such as Lyfe With Less Representative and Rapel Indonesia Manager. Keywords: Waste Management, Education, Society, Technology, Surakarta